Pengaruh Angka Harapan Hidup, Rata-Rata Lama Sekolah dan Pengangguran Terhadap Penduduk Miskin di Kabupaten Halmahera Utara - Magdeline Gloria Sipahelut; Vecky A.J Masinambow; Krest Donald Tolosang (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of life expectancy, average years of schooling, and unemployment on the poor population in North Halmahera Regency. The data used in this study are secondary time series data obtained from the Central Bureau of Statistics of North Halmahera Regency in 2009-2023. The results showed that the life expectancy rate had a significant positive effect on the poor population in North Halmahera Regency, the average length of schooling had a significant negative effect on the poor population in North Halmahera Regency, unemployment had an insignificant negative effect on the poor population in North Halmahera Regency. Simultaneously Life Expectancy, Average Years of Schooling, and Unemployment have a significant effect on the Poor Population in North Halmahera Regency.